The Phenomenon of Internet Trolling and the Spreading of Hate Speech on Social Media - Gemiharto M.Si, Ilham; M.Si, Sukaesih (International Journal of Psychosocial Rehabilitation, 2020)
Over the last few years, there is a new phenomenon in social media globally called internet troll or flaming or trolling. A troll is a person who posts provocative messages and off-topic messages on the internet, either on social media or online discussion forum, with the intention of provoking other users into displaying emotional responses or disturbing the discussion process. The internet trolls always use fake usernames, profile photos, and profile descriptions. This study researches and discusses about the phenomenon of internet troll and the spreading of hate speech on social media. The purpose of this study is to understand and to analyze the troll role in spreading the hate speech on social media in Indonesia. This study uses qualitative research method. The analytical method of this research that we used is a case study analysis based on the method, the data, and the source triangulation. The result of the study is that the term internet troll is only used by those who make comments in off-topic discussion in newsgroup. However, the term troll is currently used widely by every person who uses swearing, profanity, and hate speech in some social media platforms. The internet trolls are described to have psychological personality problem because they say harsh words easily to ruin the credibility of a person on social media.